Fracture in-situ plugging and self-repairing method based on homologous rock ore self-activation
Through the self-activated fracture sealing method of homologous rock ore, a cementing network is formed with homologous rock ore powder and low-concentration acid-base activators, the environmental compatibility and cost problems of traditional sealing technology are solved, and efficient and stable fracture sealing and self-repair are achieved, which is suitable for a variety of extreme environments.
Patent Information
- Application Number
- CN202510809584.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-08-22
AI Technical Summary
The existing crack sealing technology has environmental compatibility problems, high engineering costs, weak links caused by the differences in the interface between exogenous materials and surrounding rocks, and neglecting the potential of self-repair of rocks. Traditional MICP technology is limited in application in extreme environments.
The self-activated fracture sealing method of homologous rock ore is adopted, and the target rock layer powder is mixed with low-concentration acid-base activator to form a cementing network, using the consistency of mineral composition of geological environment, combining nanoparticles and shape memory alloy fibers to achieve self-healing, and using intelligent grouting equipment to accurately control it.
It achieves long-term stability closely integrated with surrounding rock, reduces engineering costs and ecological risks, improves process applicability and environmental friendliness, and is suitable for extreme conditions such as high temperature and acidity.
Smart Images

Figure CN120520536A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of geotechnical and geological engineering technology, and in particular to a method for in-situ crack plugging and self-repairing based on self-activation of homologous rocks and minerals. Background Art
[0002] In geotechnical engineering, oil and gas extraction, and mining development, leakage and structural instability in rock mass fractures have long plagued project safety and operational efficiency. Current mainstream crack sealing technologies rely primarily on cement-based grouting materials and organic polymers (such as epoxy resins). While these methods can achieve crack sealing to a certain extent, they suffer from numerous technical drawbacks that are difficult to overcome.
[0003] First, the environmental compatibility of traditional grouting materials is becoming increasingly prominent. Cement paste produces alkaline seepage during the curing process. This highly alkaline environment not only alters the chemical balance of groundwater but also may trigger an alkali-aggregate reaction at the rock-paste interface, leading to a decrease in the long-term stability of the sealing structure. Organic materials such as epoxy resins are prone to aging and degradation in complex geological environments, and their decomposition products may cause secondary pollution to the surrounding ecological environment.
[0004] Secondly, existing technologies are increasingly constraining project costs. For example, in tunnel engineering, the cost of traditional cement grouting materials accounts for approximately 45%-60% of the total cost of crack treatment. In specialized environments such as deep mines or offshore oil and gas fields, this proportion can reach as high as 70%. More importantly, these exogenous materials differ significantly from the surrounding rock's mineral composition, often forming distinct interfaces that can become weak links in the subsequent rock mass structure.
[0005] Although the microbial induced calcium carbonate precipitation (MICP) technology that has emerged in recent years has improved environmental friendliness to a certain extent, its application has obvious limitations: the activity of microorganisms is strictly restricted by conditions such as temperature and pH value, and they can hardly survive in high-temperature oil and gas reservoirs or acidic mining environments; and the introduction of exogenous microorganisms may destroy the underground ecological balance, and the risk of using it in sensitive areas such as drinking water sources is extremely high.
[0006] Furthermore, existing sealing technologies generally ignore the rock's inherent potential for repair. Geological research has long confirmed that clay and carbonate minerals in rocks possess the ability to self-cement under specific hydrogeochemical conditions, but traditional engineering practices have failed to effectively utilize this natural mechanism. This emphasis on human intervention over natural repair not only increases engineering complexity but also results in a significant waste of resources.
[0007] Therefore, we proposed an in-situ crack sealing and self-repair method based on self-activation of homologous rocks and minerals to solve the problems raised above.
[0008] The above information disclosed in this background technology is only for enhancing understanding of the background technology of the present invention and therefore it may contain information that does not constitute the prior art that is already known to a person of ordinary skill in the art. Summary of the Invention
[0009] The purpose of the present invention is to provide an in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals to solve the problems raised by the above-mentioned background technology.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] The in-situ crack plugging and self-repair method based on self-activation of homologous rocks and minerals is used to plug and repair cracks in tunnel surrounding rocks, mine rock masses, or oil and gas wells, and includes the following steps:
[0012] Step 1: Obtain the rock produced by crushing the target rock layer, grind it to a particle size of less than 100 μm using a vertical planetary ball mill, and obtain homologous rock powder that retains the original rock mineral components. The particle size distribution is measured by a laser particle size analyzer, and the retained silicate / carbonate mineral components are determined by X-ray diffraction;
[0013] Step 2: preparing a low-concentration acidic or alkaline activator with a pH value of 4-10, wherein the activator is an alkaline solution containing Na2CO3 or an acidic solution containing citric acid;
[0014] Step 3: Mix the homologous rock powder and the activator at a solid-liquid ratio of 1:3, and stir them in a twin-shaft mixer at a speed of 150-2000 rpm for 5-10 minutes until they are uniform and have an apparent viscosity of 500-800 mPa·s to prepare a rock powder slurry;
[0015] Step 4: Use spiral drilling and grouting integrated equipment to inject slurry into the cracks, using capillary action to achieve full coverage of fine cracks of 0.1-5mm;
[0016] Step 5: Utilize the natural temperature of the formation or an external heat source to complete the cementation reaction of the slurry within 24-72 hours, forming a cementation network containing calcite and calcium silicate, thereby achieving crack sealing and self-repair.
[0017] Preferably, 0.5-2% of nano mineral particles are added to the rock powder slurry, including at least one of nano SiO2 and nano CaCO3, with a particle size of 20-100 nm.
[0018] Preferably, the activator is a pH-responsive microcapsule sustained-release system, the microcapsule shell is made of a degradable polymer, and the citric acid or Na2CO3 solute is encapsulated, and the degradation time is 6-12 hours.
[0019] Preferably, a pulse grouting process is adopted, the grouting pressure is periodically switched between 2-15 MPa, and the duration of a single pulse is 5-10 seconds.
[0020] Preferably, the integrated spiral drilling and grouting equipment integrates three-dimensional crack scanning and AI path planning systems, obtains three-dimensional point cloud data of cracks through lidar or downhole robots, and the AI model automatically optimizes the grouting hole position, pressure gradient and slurry flow rate.
[0021] Preferably, the integrated grouting equipment has a built-in pressure feedback and constant temperature control system, the drill bit is equipped with a pressure sensor to monitor the grouting pressure in real time and automatically adjust the flow rate, and the storage tank maintains the slurry temperature at 15-80°C.
[0022] Preferably, 0.1-0.5% of shape memory alloy fibers are mixed into the rock powder slurry, and when the crack expands under dynamic load, the unreacted slurry is driven to undergo secondary cementation, thereby achieving three self-repair cycles.
[0023] Preferably, the homologous rock powder comprises one or more of quartz and calcite minerals separated from mine tailings and tunnel slag.
[0024] Preferably, CO2 gas is introduced into the alkaline activator system to fix the CO2 into calcite cement through carbonization reaction.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] In the present invention, by adopting the in-situ crushing of the target rock layer and grinding the rock into powder, the introduction of heterogeneous materials such as cement and epoxy resin is avoided. Not only is the material source wide and low-cost, but it is also consistent with the mineral composition of the geological environment. The diagenetic rock and the surrounding rock are tightly combined, and there is no interface for sufficient cementation. The long-term stability is significantly improved, and the secondary leakage or shedding problem caused by the difference in properties of traditional exogenous materials is effectively avoided. Secondly, the self-activation mechanism only requires a low-concentration acid / alkali solution with a pH value of 4-10 as a reaction medium. The cementing ions are released through chemical reactions such as calcite dissolution-recrystallization and silicate ion condensation. There is no need for microbial intervention, which simplifies the process flow while avoiding environmental restrictions and ecological risks on microbial activity. It can still stably cement under extreme conditions such as high temperature and acidity.
[0027] In the present invention, the density of the cementing network is enhanced by nano-mineral particles, the delayed reaction of deep cracks is achieved by pH-responsive microcapsule slow-release activator, and the pulse grouting process is used to break blockages and improve the coverage of complex cracks, thereby improving the accuracy and applicability of the process: nanoparticles participate in the reaction through surface hydroxyl groups, thereby improving the impermeability of the cementing body; shape memory alloy fibers trigger secondary cementation under dynamic loads.
[0028] In terms of environmental benefits, this invention's homologous rock and mineral materials avoid the alkaline contamination of traditional cement and the potential secondary environmental pollution induced by microorganisms in traditional MICP methods, aligning with green and low-carbon policy priorities. Economically, this method significantly reduces costs throughout the entire lifecycle, from material procurement, preparation, and transportation to construction and maintenance. The overall cost of tunnels, underground storage facilities, and oil and gas wells is also lower than traditional processes. Long-term stability reduces the need for remediation and maintenance, significantly reducing potential ecological restoration costs.
[0029] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Flowchart of the present invention. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts are within the scope of protection of the present invention.
[0032] See also Figure 1 ,Example 1, a mountain tunnel passes through limestone strata. After excavation, a circumferential crack with a width of 2.5 mm and a length of 8 m was found, which needed to be sealed to prevent groundwater leakage.
[0033] Step 1: Select limestone fragments produced by tunnel blasting, remove surface soil impurities, and crush them to a particle size of 5mm.
[0034] A vertical planetary ball mill was used with a rotation speed of 400 rpm, zirconia balls as the grinding medium, and a grinding time of 6 hours. The powder particle size distribution was detected by a laser particle size analyzer and was D10 = 20 μm, D50 = 60 μm, and D90 = 120 μm.
[0035] The composition was analyzed, and X-ray diffraction determined that the mineral composition was 82% calcite, 15% clay minerals, and 3% quartz, retaining the original rock cementing ions Ca 2+ 、Si 3+ .
[0036] Among them, the dissolution and cementation process of calcite in alkaline activator:
[0037] CaCO3+CO3 2-+H2O→Ca(HCO3)2→CaCO3↓+CO2↑+H2O
[0038] Step 2: Based on the alkalinity of the formation water, select alkaline activator Na2CO3 solution.
[0039] Weigh 150 g of Na2CO3 solid, dissolve it in 5 L of deionized water, stir until completely dissolved, and measure the solution pH with a pH meter to obtain a pH of 9.2.
[0040] Step 3: Weigh 5 kg of rock powder and 15 L of activator at a ratio of 1:3, pour into a twin-shaft mixer, rotate at 150 rpm, and stir for 10 minutes until the slurry is free of lumps and has an apparent viscosity of 800 mPa·s.
[0041] Step 4: Use ZSL-100 spiral drilling and grouting machine with a drill bit diameter of 32mm and equipped with a pressure sensor.
[0042] During the operation, grouting holes were arranged every 1.5m along the crack direction, with a drilling depth of 80cm and exceeding the crack depth by 20cm;
[0043] The slurry was injected at an initial pressure of 0.8 MPa and stopped after overflow from adjacent holes was observed. The grouting volume per hole was approximately 2.3 L, and the total injection time was 25 minutes.
[0044] Using capillary action and according to the Laplace equation, the capillary pressure of a 0.5mm crack is about 12kPa, achieving full coverage of microcracks.
[0045] Among them, the silicate ion condensation reaction: nH4SiO4→(SiO2)n·nH2O↓+nH2O
[0046] Step 5: The tunnel was maintained at an ambient temperature of 18°C without additional heating. After 72 hours of standing, the formwork was removed and the slurry was observed to be completely solidified and tightly bonded to the surrounding rock without any peeling.
[0047] Finally, the performance test was carried out. For compressive strength, the compression test was carried out by drilling core sampling, and the average value was 28MPa. For permeability, the water pressure test showed that the permeability was 0.005mD, which was 98% lower than before grouting. The microstructure, scanning electron microscopy showed that calcite crystals were interwoven into a network, filling the cracks and pores. Among them, the calcite crystal growth mechanism is Ca 2+ +CO3 2- →CaCO3↓
[0048] In Example 2, after fracturing, a group of micro-cracks with a width of 0.1-0.5 mm appears in a shale gas well, resulting in wellbore leakage, which needs to be sealed without damaging the reservoir.
[0049] Shale drill cuttings from the same stratum were collected and ground to a D50 of 40 μm, containing 45% illite, 35% quartz, and 20% calcite. 1.5% nano-CaCO3 particles with a particle size of 80 nm were added and evenly dispersed into the slurry using an ultrasonic disperser at 300 W for 15 minutes. A citric acid solution with a pH of 5 and a concentration of 0.03 mol / L was prepared. The hydroxyl groups on the surface of the nanoparticles participate in the cementation process:
[0050] CaCO3(nano)+H + →Ca 2+ +HCO3-Ca 2+ +SiO3 2- →CaSiO3↓
[0051] Neutralization reaction of citric acid and calcite:
[0052] C6H8O7+CaCO3→Ca3(C6H5O7)2+CO2↑+H2O
[0053] A continuous tubing grouting system is used, equipped with a constant temperature slurry storage tank, and the slurry temperature is maintained at 40°C.
[0054] The injection pressure is 15MPa and 80% higher than the formation fracture pressure to ensure that the slurry enters the micro-cracks. The grouting volume per well is 12m 3 , which took 4 hours.
[0055] Finally, the plugging success rate was 98%, the wellbore pressure was stable after grouting, and the leakage was reduced from 5m 3 / h down to 0.1m 3 / h). Regarding strength properties, the compressive strength of the cemented structure was 22 MPa. Core flow tests revealed a 95% reservoir permeability recovery, demonstrating that the acidic activator did not cause clay expansion or blockage.
[0056] Example 3: In a metal mine tunnel, affected by blasting vibration, cracks in the surrounding rock periodically expand to a width of 1-3 mm and a vibration frequency of 3-5 Hz.
[0057] Add 0.2% Ni-Ti to shape memory alloy fibers with a diameter of 30 μm and a length of 1.5 mm, and pre-deform the fibers by 8%. Add homologous sandstone powder (D50 = 50 μm) to a Na2CO3 solution with a pH of 8, with a solid-liquid ratio of 1:3.5.
[0058] A high-pressure pulse of 20 MPa is applied for 5 seconds to break the brittle shell formed by the initial cementation; a low-pressure pulse of 2 MPa is applied for 30 seconds to fill the newly generated microcracks using capillary action; the cycle is repeated 3 times, and the total grouting time is extended by 20% compared with the traditional process.
[0059] Vibration simulation was performed by applying a sinusoidal load of 5 Hz and 1 mm amplitude for 2 hours using an electromagnetic vibration table.
[0060] After the first vibration, the crack expanded to 0.6mm and automatically cemented within 24 hours; after the third vibration, the crack width stabilized at 0.3mm, and the compressive strength retention rate of the cementing body was 92%; SEM observation showed that a secondary cementing ring was formed around the alloy fiber, proving that the strain energy-driven repair mechanism is effective.
[0061] Among them, alloy deformation triggers the cementation of the remaining slurry:
[0062] Ca 2+ (Residual)+SiO 32- (residue) → CaSiO3↓ (secondary cementation)
[0063] Primary cementation reaction: Ca2++CO 32- →CaCO3↓(brittle shell)
[0064] Secondary cementation reaction: Ca 2+ +Al 3+ +SiO 32- +H2O→Calcium aluminosilicate hydrate (tough cement)
[0065] Example 4: a crack between the casing of a hot dry rock geothermal well and the annulus of the surrounding rock, with a temperature of 150° C. and a formation water salinity of 30 g / L.
[0066] Granite fragments containing 35% orthoclase, 25% quartz, 20% biotite and 20% forsterite were selected and ground to D50 = 70 μm, with an upper temperature resistance of 180°C.
[0067] The activator is a 0.15 mol / L NaOH solution with a pH of 10, and CO2 gas is introduced until the solution becomes turbid to generate NaHCO3.
[0068] At a formation temperature of 80°C, the slurry began to cement 3 hours after injection and solidified within 24 hours. XRD analysis showed that the cement was 55% calcite, 35% calcium silicate, and 10% forsterite. The CO2 storage capacity was 0.25 kg / m 3 Slurry, equivalent to absorbing 10m 3 CO2 in the air.
[0069] Among them, the neutralization reaction of CO2 and strong base is CO2+2NaOH→Na2CO3+H2O
[0070] Na2CO3+CO2+H2O→2NaHCO3
[0071] Mineralization reaction of forsterite and CO2: Mg2SiO4+2CO2+2H2O→2MgCO3+H4SiO4
[0072] In the present invention, for large-scale processing of raw materials, an automated production line for rock and ore crushing, grinding, and screening is established, equipped with a large planetary ball mill and an intelligent sorting system to achieve standardized production of homologous rock and ore powders.
[0073] Industrial-grade Na2CO3 and food-grade citric acid can be used, and large-scale procurement can be used to reduce reagent costs. Multiple types of activators can be designed for rapid adaptation to different geological environments. Furthermore, the production capacity of nano-mineral particles (nano-SiO2, nano-CaCO3) and shape memory alloy fibers can be expanded, and standardized production processes can be established to reduce additive costs.
[0074] The integrated spiral drilling and grouting equipment is equipped with a multi-channel grouting system and an intelligent batching device to automatically adjust the solid-liquid ratio. The IoT-based grouting monitoring system uses pressure, temperature, and flow sensors to monitor the grouting process in real time, providing pressure feedback and constant temperature control.
[0075] A process parameter database, including slurry ratio, grouting pressure, and pulse frequency, was established for different application scenarios, such as tunnel surrounding rock, mining rock, and oil and gas wells. Construction and quality acceptance specifications for plugging projects were developed, clarifying indicators for material inspection, construction process control, and performance evaluation. An environmental monitoring system was established during construction to ensure compliance with environmental protection requirements. Furthermore, equipment operation safety procedures and emergency response plans were developed to ensure the safety of construction personnel.
[0076] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0077] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for in-situ sealing and self-repairing of fractures based on self-activation of homologous rocks and minerals, characterized in that: It is used to seal and repair cracks in tunnel surrounding rock, mine rock mass or oil and gas wells, and includes the following steps: Step 1: Obtain the rock produced by crushing the target rock layer, grind it to a particle size of less than 100 μm using a vertical planetary ball mill, and obtain homologous rock powder that retains the original rock mineral components. The particle size distribution is measured by a laser particle size analyzer, and the retained silicate / carbonate mineral components are determined by X-ray diffraction; Step 2: preparing a low-concentration acidic or alkaline activator with a pH value of 4-10, wherein the activator is an alkaline solution containing Na2CO3 or an acidic solution containing citric acid; Step 3: Mix the homologous rock powder and the activator at a solid-liquid ratio of 1:3, and stir them in a twin-shaft mixer at a speed of 150-2000 rpm for 5-10 minutes until they are uniform and have an apparent viscosity of 500-800 mPa·s to prepare a rock powder slurry; Step 4: Use spiral drilling and grouting integrated equipment to inject slurry into the cracks, using capillary action to achieve full coverage of fine cracks of 0.1-5mm; Step 5: Utilize the natural temperature of the formation or an external heat source to complete the cementation reaction of the slurry within 24-72 hours, forming a cementation network containing calcite and calcium silicate, thereby achieving crack sealing and self-repair.
2. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: 0.5-2% of nano mineral particles are added to the rock powder slurry, including at least one of nano SiO2 and nano CaCO3, with a particle size of 20-100 nm.
3. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: The activator is a pH-responsive microcapsule sustained-release system. The microcapsule shell is made of a degradable polymer and encapsulates citric acid or Na2CO3 solute. The degradation time is 6-12 hours.
4. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: A pulse grouting process is adopted, and the grouting pressure is periodically switched between 2-15MPa, and the duration of a single pulse is 5-10 seconds.
5. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: The integrated spiral drilling and grouting equipment integrates three-dimensional crack scanning and AI path planning systems, obtains three-dimensional point cloud data of cracks through lidar or downhole robots, and the AI model automatically optimizes the grouting hole position, pressure gradient and slurry flow rate.
6. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: The integrated grouting equipment has a built-in pressure feedback and constant temperature control system. The drill bit is equipped with a pressure sensor to monitor the grouting pressure in real time and automatically adjust the flow rate. The storage tank maintains the slurry temperature at 15-80°C.
7. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: 0.1-0.5% of shape memory alloy fibers are mixed into the rock powder slurry, which drives the unreacted slurry to undergo secondary cementation when cracks expand under dynamic load, thereby achieving three self-repair cycles.
8. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: The homologous rock powder comprises one or more of quartz and calcite minerals separated from mine tailings and tunnel slag.
9. The in-situ crack plugging and self-repairing method based on self-activation of homologous rocks and minerals according to claim 1 is characterized by: CO2 gas is introduced into the alkaline activator system and fixed into calcite cement through carbonization reaction.
Citation Information
Cited By
Wrapping assembly for porous fractured rock sample in flexible loading mode and circumferential strain correction method
CN121207727A